2015
DOI: 10.3758/s13421-015-0538-y
|View full text |Cite
|
Sign up to set email alerts
|

Does the isolation effect require attention?

Abstract: An item that differs from the surrounding items is remembered better than an item that is consistent with its surroundings; this is known as the von Restorff effect or isolation effect (von Restorff, Psychologische Forschung, 18, 299-342, 1933). Theoretical explanations have proposed that the isolate is processed differently from control items, though some research has suggested that this processing might require more attention for semantic than for physical isolates. To test this possibility, in the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 46 publications
(83 reference statements)
3
12
1
Order By: Relevance
“…Whereas ample evidence exists for retro-cueing particular objects in VWM, previous evidence for an effect of dimension-based retro-cues has been scarce and ambiguous. In one recently published study by Pilling and Barrett 46 , retro-cueing a feature dimension yielded no effect on performance in a change-detection task, whereas retro-cueing-benefits were observed for a sameness detection. In the present task, we used a continuous reproduction task and demonstrate that the influence of feature dimension based retro-cues in VWM is robust, for both colour and orientation dimensions.…”
Section: Discussionmentioning
confidence: 90%
“…Whereas ample evidence exists for retro-cueing particular objects in VWM, previous evidence for an effect of dimension-based retro-cues has been scarce and ambiguous. In one recently published study by Pilling and Barrett 46 , retro-cueing a feature dimension yielded no effect on performance in a change-detection task, whereas retro-cueing-benefits were observed for a sameness detection. In the present task, we used a continuous reproduction task and demonstrate that the influence of feature dimension based retro-cues in VWM is robust, for both colour and orientation dimensions.…”
Section: Discussionmentioning
confidence: 90%
“…Some stimulus contrasts may be coded relatively easily or even automatically. Bireta and Mazzei (2015) reported that midlist isolation by conceptual category did not enhance recall when participants were performing a distracting task at encoding. However, they observed the physical isolation effect using contrasts in font color between the isolates and background words under distracted conditions at encoding.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the isolation effect either decreases or disappears when cognitive resources are limited, depending on the nature and retrieval advantages of the comparison list. Bireta and Mazzei (2015) also demonstrated that the isolation effect depends on having sufficient cognitive resources available to process stimulus changes within a list. Participants in their study recalled words that were either physically isolated (a red word embedded in a list of black words) or conceptually isolated (a word from one category presented in a list of words from a contrasting category).…”
Section: Attention and The Midlist Isolation Effectmentioning
confidence: 99%
“…Relevant to clinical/educational assessment in general and pediatric ADHD in particular, working memory underlies learning skills such as math and reading attainment (Raghubar et al, 2010; Sesma et al, 2009; Swanson & Kim, 2007), science (Gathercole et al, 2004), written language (Alloway et al, 2005), oral language (McInnes et al, 2003), and following directions (Jaroslawska et al, 2016). In contrast, short-term memory usually demonstrates weaker relations with reading and math achievement, and is generally unrelated to comprehension and complex learning (Rapport et al, 2013).…”
Section: Working Memory Vs Short-term Memorymentioning
confidence: 99%